2017
DOI: 10.1007/s00268-017-4293-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surgical Lighting on Intraoperative Safety in Low‐Resource Settings: A Cross‐Sectional Survey of Surgical Providers

Abstract: In our survey of surgeons working in low-resource settings, a majority report poor surgical lighting as a major risk to patient safety and nearly one-third report delayed or cancelled operations due to poor lighting. Developing and distributing robust, affordable, high-quality surgical headlights could provide an ideal solution to this significant surgical safety issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Erim, Kolapo, and Resch (2012) observed in a descriptive cross-sectional study that over two thirds of Nigerian healthcare facilities lacked an uninterrupted supply of electricity, leaving them unable to provide basic emergency obstetric care services, and the majority of those affected were primary care facilities (Erim et al, 2012). Furthermore, a descriptive cross-sectional study by Forrester et al (2017) investigating the impact of electricity failures on surgical lighting and patient care in 39 low-resource countries in Africa revealed that poor surgical lighting due to unreliable power was considered a significant risk to patient safety, potentially leading to unintended blood loss, intestinal spillage, and nerve damage (Forrester et al, 2017). Although 94% of surveyed surgical providers reported that their facility had a backup generator, just 48% of these generators were always available to use.…”
Section: Health Effects Of Electricity Reliabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Erim, Kolapo, and Resch (2012) observed in a descriptive cross-sectional study that over two thirds of Nigerian healthcare facilities lacked an uninterrupted supply of electricity, leaving them unable to provide basic emergency obstetric care services, and the majority of those affected were primary care facilities (Erim et al, 2012). Furthermore, a descriptive cross-sectional study by Forrester et al (2017) investigating the impact of electricity failures on surgical lighting and patient care in 39 low-resource countries in Africa revealed that poor surgical lighting due to unreliable power was considered a significant risk to patient safety, potentially leading to unintended blood loss, intestinal spillage, and nerve damage (Forrester et al, 2017). Although 94% of surveyed surgical providers reported that their facility had a backup generator, just 48% of these generators were always available to use.…”
Section: Health Effects Of Electricity Reliabilitymentioning
confidence: 99%
“…Although 94% of surveyed surgical providers reported that their facility had a backup generator, just 48% of these generators were always available to use. As a result, delays and cancellations due to poor lighting were common (Forrester et al, 2017). Finally, using a non-randomised controlled trial to investigate the effects of a programme intended to increase the hours of supply and voltage stability of electricity in health facilities in India, Chen et al (2019) found that exposure to the programme significantly increased the probability of primary health centres having a functioning deep-freezer, refrigerator, cold box, and vaccine carrier, as well having functioning operating and delivery tables, all of which are necessary in order to provide care.…”
Section: Health Effects Of Electricity Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Basic infrastructure for surgery is frequently in short supply, limiting the consistency with which healthcare facilities can provide basic surgical care42 ; as an example, running water was only available in 50% of Gambian health facilities,43 and oxygen supplies with masks and tubing were available in only 26% of Rwandan health facilities 44. High rates of delayed or cancelled procedures in LMICs have been shown to arise through both poor infrastructure45 46 and equipment shortages 46…”
Section: Need Access and Qualitymentioning
confidence: 99%
“…). Regional hospitals usually have access to electricity (although inconsistently), safe water, and steam sterilization. Low‐cost sterile surgical gloves, reusable cloth drapes and gowns, and iodophor‐based aqueous surgical‐site solutions are typical but may be in short supply.…”
Section: Introductionmentioning
confidence: 99%